Blazing The Trail For Astronomy Education Research (Journal of Astronomy & Earth Sciences Education, 2015)
Education research has long considered student learning of topics in astronomy and the space sciences, but astronomy education research as a sub-field of discipline-based education research is relatively new. Driven by a growing interest among higher education astronomy educators in improving the general education, introductory science survey course for non-science majoring undergraduates (“ASTRO 101”), contemporary astronomy education research is led by scholars with significant expertise in astronomy content. In this review, we outline the recent history of the growing field of discipline-based astronomy education research by analyzing graduate degrees earned, faculty involved, and major milestones, such as the appearance of archival, peer-reviewed professional journals. Astronomy education research as a field of discipline-based education research has made notable strides in the past few decades that distinguish it from the K-12 education research realm, and, in spite of some setbacks, continues to move forward as a growing and vibrant community of scholars.
Keywords: Astronomy Education; History of Discipline-Based Education Research; ASTRO 101